A study of voiceless inter-dental fricative [θ], [ð] sounds and alveolar liquid [r] sound among Chinese learners of English at a higher educational institution in Malaysia - Mizanur Rahman; Md Kamrul Hasan (Politeknik Negeri Bali, 2019)
This study aims to investigate the pronunciation mistakes in English in accordance with the phonetic study of voiceless and voiced inter-dental fricatives [θ], [ð] and alveolar liquid [r] sounds among Chinese learners of English at University Utara Malaysia (UUM). In order to find out non-native English leaner pronunciation errors, these errors reflect the interference of different sound systems on English pronunciation. Speech samples of the subjects’ pronunciation were taken through words in terms of [θ], [ð] and [r] sounds. Data was collected by contracting survey through structure; six Chinese students were selected by using non-probability convenient sampling technique. Using a reading 30 wordlist worksheets as the instrument of this research, the respondents’ pronunciation was observed and assessed by using native/ phonetics expert speaker and also ensured by the evaluation form. In addition, data of this study was analysed by SPSS (22 version) software package. Data was collected and analysed with the guidance of phonemic transcription of Cambridge English Pronouncing Dictionary. Using different pronunciation analysis, potential difficulties of English pronunciation for the three subjects were listed by comparing the sound systems of English among Chinese learners. Moreover, the pronunciation errors of subjects were diagnosed into categories based on Error Analysis. The findings would help to provide a clear understanding of the common characteristics of pronunciation errors made by the subjects. Finally, some recommendations have been proposed to overcome the pronunciation difficulties of non-native English learners.